Evaluation of Chitosan as a Natural Disintegrant in the Formulation of Aspirin Orally Disintegrating Tablets - Desy nawangsari; Hazim Fikri Alfianto; Ayu Pujianti; Nur Rahmawati; Deva Krisna Kadarani (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
Aspirin is an antiplatelet that is used for the therapy and prevention of stroke, many strokes occur in elderly people. Orally Disintegrating Tablet (ODT) can be dissolved quickly making it easier for geriatric patients to swallow. This study aims to determine the effect of variation in the concentration of chitosan as a disintegrating agent on the physical properties of ODT aspirin. Aspirin ODT tablets were produced by direct compression in 3 formulas with variations of chitosan of 3.5%, 7% and 14%. The results showed that a chitosan concentration of 3.5% yielded optimal tablet properties: disintegration time of 23.66 seconds, friability of 0.41%, and dissolution of 96.81%. Statistically significant differences (p < 0.05) were observed among the formulations in terms of in hardness (p = 0.027), friability (p = 0.010) and disintegration time (p = 0.000). The disintegration mechanism of chitosan involves swelling, wicking, and strain recovery. At lower concentrations, chitosan promotes rapid water uptake and particle expansion, facilitating fast breakdown of the tablet matrix. In contrast, higher chitosan levels may induce gel formation that hinders water penetration, thus delaying disintegration. In conclusion, chitosan at a concentration of 3.5% effectively functions as a natural disintegrant in aspirin ODTs, offering rapid disintegration and high dissolution, which is suitable for geriatric patients with swallowing difficulties.